Structure and content of professional teaching competence of in-company teachers at industrial enterprises - А. G. Kolzina; О. F. Shikhova; А. А. Gareyev; Yu. А. Shikhov; M. G. Rodríguez Bulnes (Russian State Vocational Pedagogical University, 2022)
Introduction. The concept of lean management, which is focused on optimising and improving manufacturing processes, can be applied to the management of in-company further professional training. Within this training, in-company teachers are more often called upon to teach enterprise employees. Thanks to this, education services are provided at short notice and their high quality is guaranteed at minimum expenses. However, this is possible only if the level of professional teaching competence of these in-company teachers is significantly high. At the moment, the structure and content of this competence are not justified didactically and are not regulated by normative documents. Given that teaching is not the primary job of in-company teachers, and most of them are not trained professionally as teachers, it should be emphasised that the problem of identifying and evaluating the most significant components of professional teaching competence for in-company teachers, the components being the goal of effective advanced education training, is highly relevant today.The aim of this research was to present the structure and content of professional teaching competence for in-company teachers at modern industrial enterprises.Methodology and research methods. Competency-based, activity-based and qualimetric approaches have been chosen as the methodological basis of this research, as they help implement the principles of professional orientation, optimisation and advanced nature of in-company teacher training. The qualimetric approach is used as a leading approach which implies the use of the method of group expert evaluation to organise the teaching expert evaluation of the structure and content of professional teaching competence of an in-company teacher. The authors used pedagogical expertise procedures with the involvement of in-company training customers as experts: enterprise managers, trainees and training organisers. The selection of qualified experts in the field of in-company training was carried out by the methods of self-assessment and reasoning assessment.Results. The structure of professional teaching competence of an in-company teacher has been defined and includes the most significant components: gnostic, communicative, evaluative and design ones. These components specify the types and tasks of teaching activity at an enterprise and can guide the design of individual educational trajectories. The types of individual educational trajectories have been suggested to train in-company teachers (basic, technological, communication-based, and evaluation-based), which can be chosen based on their education level, professional experience and their level of motivation for teaching activity.Scientific novelty of the study is in justifying the structure and content of professional teaching competence of in-company teachers by the expert method. These structure and content take into account the demands of employers for training such specialists at industrial enterprises, a special type of learners and the principles of lean management.Practical significance. The content of professional teaching competence components, which defines specific didactic goals concerning their development, can be taken into account when designing the training and professional development programmes for in-company teachers and planning their organisational and procedural guidance around their individual educational trajectories.